TOTAL ECONOMIC VALUATION OF THE POLLUTED MANGROVE ECOSYSTEM IN BANDAR BAKAU DUMAI - Fitri Herliza; Trisla Warningsih; Lamun Bathara (Asian Journal of Aquatic Sciences, 2026)
This study aims to calculate the Total Economic Value (TEV) of the polluted mangrove ecosystem in Bandar Bakau Dumai, Riau Province. Mangrove ecosystems provide important ecological and economic services but face serious threats from pollution from industrial activities, domestic waste, and plastic waste. This study uses the Total Economic Value approach, which includes Direct Use Value (DUV), Indirect Use Value (IUV), and Opportunity Value (OV). Data was collected through surveys, interviews with 14 respondents, and secondary data analysis. The results show that the TEV of the mangrove ecosystem is IDR 468,960,000/year, or approximately IDR 15,128,387/ha/year. The DUV component of IDR 147,700,000 is derived from the utilization of shrimp, kedabu fruit juice, and nyirih leaves. The IUV of IDR 320,000,000 reflects services for coastal protection and the provision of marine biota habitat. Meanwhile, the OV of IDR 1,260,000 indicates the community's willingness to pay for conservation. This value confirms that, despite pollution, mangrove ecosystems continue to provide significant economic benefits and should be prioritized in conservation and sustainable management policies.